Localization of employee salaries and its impact on the deposits banks: (a sample of Iraqi private banks) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research problem consisted in answering the question that revolves around what is the impact of localizing employees’ salaries on bank deposits, and did it lead to an increase in their size? The research also aimed to nominate some initial solutions to improve the role of salary localization, in terms of reviewing the concept of electronic payment systems, its tools and channels, and then identifying the concept of salary localization, its importance, objectives and obstacles to its application, and then analyzing the reality of the state of localization of salaries and bank deposits to banks, the research sample for the period (2017- 2021), and the use of the statistical program (SPSS V25) to test the research hypotheses. The study relied on the inductive approach and the descriptive analytical method in the study and analysis of information and data in the available literature on research concepts, methods of measuring it to determine the level of salary localization, and analysis of bank deposit data. The study found a set of results, the most important of which are: A significant (statistically significant) effect of the independent variable (salary settlement) was achieved on the dependent variable (the volume of bank deposits) on the total level of the six sample banks.